Optimal Point of Insertion and Needle Angle in Neuraxial Blockade Using a Midline Approach. Issue 2 (June 2018) - Vogt, M.; van Gerwen, D.J.; Lubbers, W.; van den Dobbelsteen, J.J.; Hagenaars, M.
Abstract : ( Reg Anesth Pain Med . 2017;42(5):600–608) When using a midline approach to neuraxial blockade, as few attempts as possible should be made to ensure patient comfort and reduce the risk of complications. This approach can be difficult, however, due to both patient factors beyond the clinician's control as well as equipment used, clinician experience, the positioning of the patient, and point of insertion. While there are suggested needle insertion points and angles, none are supported by clinical research. This study aimed to establish a scientific rationale for choosing the optimal insertion angle and insertion point for access to the subarachnoid space or the epidural space by using a computer algorithm to perform measurements in computed tomography (CT) scans in 52 patients at different spine levels.